Survey of ICT and Education in Africa : Benin Country Report - Tutu Agyeman, Osei (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Benin was the first country in West Africa to connect to the internet, which it did in 1995. However the weak legal and investment framework stalled progress and development of its ICT sector. Currently, deployment and integration of ICTs in education are at their lowest from the primary to the tertiary levels. While donor support helped realize some amount of meaningful connectivity to the internet, the necessary contribution from ministerial and government agency sources that should have contributed to advance the cause failed because they were inept at delivering on their assigned roles. Connectivity to the Third Semi-arid Tropics (SAT-3) submarine cable has made permanent connection to the internet via Asymmetrical Digital Subscriber Line (ADSL) a possibility and has reduced service charges considerably. This may provide a way forward from a seemingly intractable situation.